EMOB-UX: Methodological Adaptation and Systematization of Usability Patterns, Guidelines, and Heuristics in E-commerce for Urban Mobility Contexts —A Case Study in Road Toll Systems - Silva, Lucas Quadros; Morandini, Marcelo (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2026)
Research Context: The digitalization of urban mobility services, especially in toll e-commerce systems, introduces complex rules, regulatory requirements, and sociotechnical diversity. This scenario demands solutions integrating technology, processes, and people, grounded in usability and user experience. Scientific and/or Practical Problem: Generic usability patterns, guidelines, and heuristics do not adequately address domain-specific aspects such as tariff variability, regulatory interoperability, and user heterogeneity, which compromises effectiveness and digital inclusion. Proposed Solution and/or Analysis: The study adapted and applied the EMOB-UX method to the e-commerce domain in urban mobility, with emphasis on toll roads. It developed, validated, and delivered a systematized set of usability patterns, guidelines, and heuristics, configuring a scientific artifact that supports both the design and evaluation of digital systems in this context. Related IS Theory: The work aligns with IS theories on acceptance and success of digital systems, such as the DeLone and McLean IS Success Model, the Unified Theory of Acceptance and Use of Technology (UTAUT), the Diffusion of Innovations, and Task–Technology Fit (TTF). Research Method: The study was empirical-applied, exploratory, and mixedmethod, with an experimental technical procedure. EMOB-UX was structured into eight stages, including scope review, heuristic evaluation, interviews, usability tests, and questionnaires, with triangulation of qualitative and quantitative data. Summary of Results: Seven patterns were consolidated by interface components, complemented by consolidated guidelines (organization, responsiveness, feedback, accessibility, security) and emergent ones (sustainability, AI, automation). Ten domain-specific heuristics were also proposed: five novel and five adapted from Nielsen. Prototype applications showed improvements in effectiveness, efficiency, and user satisfaction. Contributions and Impact to IS Area: The study delivers a validated and systematized artifact, associated with a replicable methodological process, providing a theoretical and practical basis for regulated contexts and contributing to IS Grand Challenges in digital inclusion and governance of digital services.